KESIAPSIAGAAN MASYARAKAT TERHADAP BENCANA TSUNAMI DI KELURAHAN PASIR PUTIH, MANOKWARI - Erikha Maurizka Mayzarah; Philipus Samuel Max Batmomolin (Universitas Negeri Gorontalo, 2021)
Manokwari Regency is one of the districts in West Papua Province which has the potential for moderate to high Tsunami vulnerability. One of the vulnerable districts is East Manokwari District. Potential disaster vulnerability in an area should be followed by community preparedness. This is because when a disaster occurs, the community already understands what steps to take. This study aims to determine the level of overall preparedness of the community in Pasirido Village, East Manokwari District. This research was conducted for one month in January 2021 in Pasirido Village, East Manokwari District, Manokwari Regency. This research uses quantitative methods. The sample was determined using the method of puposive sampling with the category of the head of the family and has lived for 10 years in Kampung Pasirido so that a total sample of 30 respondents. Data collection was carried out by distributing questionnaires and interviews to respondents. The questionnaire used is a standard from LIPI-UNESCO / ISDR 2006 with parameters of knowledge and attitude (KA), emergency response plan (EP), disaster warning (WS), and resource mobilization (RMC). The results showed that the level of community preparedness on the parameters of knowledge and attitude was mostly in the very ready category of 67%. The level of community preparedness in the parameters of the emergency response plan was mostly in the very ready category of 60%. The level of community preparedness for disaster warning parameters in the very ready category was 93%. The level of community preparedness on the parameter of resource mobilization was mostly in the ready category of 80%. Based on these four categories, overall community preparedness for flood disasters is included in the very ready category of 77%. The recommendation of this study is the need to increase community preparedness by conducting training to simulations from related agencies to the community. This is so that all people in Pasirido Village are in the category of being very prepared to face the Tsunami disaster.